2019
DOI: 10.2196/10321
|View full text |Cite
|
Sign up to set email alerts
|

Mobile App for Improved Self-Management of Type 2 Diabetes: Multicenter Pragmatic Randomized Controlled Trial

Abstract: BackgroundAs the increasing prevalence of type 2 diabetes mellitus has put pressure on health systems to appropriately manage these patients, there have been a growing number of mobile apps designed to improve the self-management of diabetes. One such app, BlueStar, has been shown to significantly reduce hemoglobin A1c (HbA1c) levels in small studies and is the first app in the United States to receive Food and Drug Administration approval as a mobile prescription therapy. However, the impact of the app across… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
158
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(197 citation statements)
references
References 36 publications
1
158
0
7
Order By: Relevance
“…BlueStar is an in-app diabetes coach available for Android and iOS devices. This was the first mobile app in the USA to be given FDA approval as a mobile prescription therapy [30]. In the BlueStar app, patients can enter their blood glucose levels (wirelessly or manually) and receive real-time coaching.…”
Section: Bluestarmentioning
confidence: 99%
See 1 more Smart Citation
“…BlueStar is an in-app diabetes coach available for Android and iOS devices. This was the first mobile app in the USA to be given FDA approval as a mobile prescription therapy [30]. In the BlueStar app, patients can enter their blood glucose levels (wirelessly or manually) and receive real-time coaching.…”
Section: Bluestarmentioning
confidence: 99%
“…In a randomized multicenter controlled trial with 110 participants in the immediate treatment group (ITG), who used the app for 6 months, and with 113 in the wait-list control (WLC) group, who received usual care for the first 3 months and then used the app for the last 3 months of the study, HbA1c levels did not show evidence of reduction at 3 months (mean difference [ITG -WLC] -0.42, 95% CI -1.05 to 0.21; p = 0.19). Additionally, no effect was proven on diabetes self-management, quality of life, and healthcare utilization behaviors [30]. Older studies had shown significant HbA1c reduction [32] and improvement in self-efficacy [31].…”
Section: Bluestarmentioning
confidence: 99%
“…All recommendations were delivered through smart phone apps. In recent years using mobile apps for improving health-related problems has grown signi cantly [53][54][55]. In essence using these apps for HTN patients also is not an exception.…”
Section: Discussionmentioning
confidence: 99%
“…Few short-term research studies have reported on the preliminary efficacy of mobile phone apps either in relation to overall DSM activities or for single self-management activity change (e.g., dietary or physical activity only). Agarwal et al [50] and Faridi et al [51] tested the effect of a mobile technology on overall DSM, while others have monitored diet [52] or physical activity [52] as part of program evaluation for diabetes support. Preliminary efficacy results of these apps vary from none [50] to moderate [51,52] among participants in the intervention settings.…”
Section: Preliminary Efficacymentioning
confidence: 99%
“…Agarwal et al [50] and Faridi et al [51] tested the effect of a mobile technology on overall DSM, while others have monitored diet [52] or physical activity [52] as part of program evaluation for diabetes support. Preliminary efficacy results of these apps vary from none [50] to moderate [51,52] among participants in the intervention settings. Therefore, the significant improvements in DSM observed in our study are unique and they could be termed to have clinical significance when viewed in the context of impact on diabetes management.…”
Section: Preliminary Efficacymentioning
confidence: 99%